The Role of the Director and His Impact on the Dramaturgy of the Slovak National Theatre in the Interwar Period - Ščepán, Michal (Historical Studies on Central Europe, 2022)
The most important cultural establishment in Slovakia, the Slovak National Theatre (SNT), was founded in 1920. The beginnings of this institution were extremely complicated because its activities were not managed by the state, but by a private company called the Cooperative of the Slovak National Theatre. This joint company was founded in 1919 and consisted of representatives of the then governing bodies, the Slovak intelligentsia, and representatives of banks and other associations. In the first two seasons, the Cooperative was dealing with operation issues, mostly with obtaining the financial resources needed. The complete artistic program was in the hands of the first director of the SNT, Bedřich Jeřábek (1920–1922). During this period, however, we cannot talk about the profiling of the dramaturgy of opera and operetta on the SNT stage. This period was followed by that of directors and private entrepreneurs Oskar Nedbal (1923–1930) and Antonín Drašar (1931– 1938), who due to the financial incompetence of the Cooperative, took the management of the SNT fully into their own hands. Both directors, together with the heads of the opera ensembles, preferred modern and experimental dramaturgy, including the latest works of art. Whereas Drašar used a pragmatic approach to resolving the theatre’s financial problems, for Nedbal caused the loss of his function and life. This study deals with the comparison of the work and theatre management of individual directors in the interwar period, with an emphasis on opera and operetta dramaturgy.